The Dangers of Usury from an Economic Perspective - Arif Syofyan Hadi; Sutrisno Ismail (International Forum of Researchers and Lecturers, 2025)
The study of usury in Islamic jurisprudence (fiqh) of muamalah maliyah is crucial as it helps determine whether a transaction is permissible in Islamic business and finance. If a transaction involves elements of usury, it is considered prohibited (haram) under Islamic law. This research uses a library research method, analyzing secondary data from books, articles, and journals to review the dangers of riba from an economic perspective. The study reveals that riba occurs in sale and purchase transactions when goods or prices are manipulated, leading to unfair advantages for one party. Riba includes both usury fadl (excessive goods) and nasi'ah (delayed payment) and is prohibited in Islam, as stated in the Qur'an, Sunnah, and Ijma'. Allah's prohibition of usury aims to protect the welfare of society, and violating this law brings harm not only in this world but also in the afterlife. The widespread practice of usury contributes to economic inequality, inflation, economic stagnation, crises, and increasing debt burdens.